한국 원격 개방대학의 기원 - 남신동(Sindong Nam) (평생학습사회, 2009)
본 연구는 한국방송통신대학교의 창설과정(1968～1972)에 대한 고찰을 통해 한국 원격개방대학의 기원을 분석하였다. 원격개방대학 이념형의 세 가지 축을 ‘원격’, ‘개방’, ‘대학’으로 전제하였으며, 1972년에 창설된 한국방송통신대학교에서 이 세 가지 이념형이 특정한 방식으로 접합된 과정에 주목하였다. 한국 최초 원격개방대학의 기원을 분석하기 위해 설명수준을 효시, 계기, 동인으로 구분하였다. 한국 사회에서 등장한 최초 원격개방대학은 외국의 사례를 모방한 것이라기보다는 근현대 한국 교육사 내부에서 태동한 자생적인 산물이다. 해방 전후 방송교육, 통신교육의 사례 중에서 원격개방대학의 맹아에 해당되는 대학확장형 형태의 통신학부가 자생적으로 존재하였다. 한국 최초의 원격개방대학이 국립 대학교 부설 통신학부 형태로 출현한 계기와 조건은 1960년대 이후 ‘중등교육 팽창과 고등교육 억제’라는 한국 교육의 특수한 상황에서 주어졌다. 애초 국가 교육정책 수준에서 마련된 ‘대학통신교육제’의 시안은 재수생 구제조치로 구상되었으나, 대학자강에 의해 방송통신대학은 성인학습자 본위의 개방형 대학으로 창설되었다. 방송통신대학이 개교 후에 짧은 시기 동안에 세계 수준의 원격개방대학으로 급속하게 성장할 수 있었던 동인은 민간영역에서 분출된 교육열의 자기전개과정이다. How was Korea National Open University (Hereinafter referred to as “KNOU”) able to develop into Korea’s most representative open university after being originally established as a solution to the problems of students who failed university entrance exam? In order to answer this question, this study has classified subject matter into 3 categories, i.e. the origin of KNOU, system development and its execution, and examined a series of incidents and moments at the current levels based on the methodology of historical sociology. KNOU’s idea of open university was materialized through the university’s subjective efforts rather than through any government education policy. In 1968, the government centrally controlled the higher education opportunity to limit the number of university students; however, when the number of students who failed university entrance exam increased, the government embodied 'Air and Correspondence College' as a 2‐year junior college attached to Seoul National University to solve the social problems related to the university entrance procedure. Professors belonging to the college of education of Seoul National University including Seo Myeong‐won, the Chairman of the KNOU founding committee and Kim Jong‐seo, the first President and other social education practitioners devised a part‐time student‐centered Open University and systematically developed it. As a result, KNOU was launched in 1972 as a junior college open to all. Throughout its history, KNOU has used an open entrance system and distance teaching methods to deliver a higher education opportunity to the general public who have lost opportunities to go to school due to economic or other reasons. In 1994, the english name of the university was changed to ‘Korea National Open University’ by the efforts of the university to better reflect its purpose. KCI Citation Count: 3